Multicentre study of perioperative versus adjuvant chemotherapy for resectable colorectal liver metastases. Issue 5 (14th May 2019) - Allard, M-A; Nishioka, Y; Beghdadi, N; Imai, K; Gelli, M; Yamashita, S; Kitano, Y; Kokudo, T; Yamashita, Y-I; Sa Cunha, A; Vibert, E; Elias, D; et al.
Abstract: Background: It is not known whether perioperative chemotherapy, compared with adjuvant chemotherapy alone, improves disease-free survival (DFS) in patients with upfront resectable colorectal liver metastases (CLM). The aim of this study was to estimate the impact of neoadjuvant 5-fluorouracil, leucovorin and oxaliplatin (FOLFOX) on DFS in patients with upfront resectable CLM. Methods: Consecutive patients who presented with up to five resectable CLM at two Japanese and two French centres in 2008–2015 were included in the study. Both French institutions favoured perioperative FOLFOX, whereas the two Japanese groups systematically preferred upfront surgery plus adjuvant chemotherapy. Inverse probability of treatment weighting (IPTW) and Cox regression multivariable models were used to adjust for confounding. The primary outcome was DFS. Results: Some 300 patients were included: 151 received perioperative chemotherapy and 149 had upfront surgery plus adjuvant chemotherapy. The weighted 3-year DFS rate was 33·5 per cent after perioperative chemotherapy compared with 27·1 per cent after upfront surgery plus adjuvant chemotherapy (hazard ratio (HR) 0·85, 95 per cent c.i. 0·62 to 1·16; P = 0·318). For the subgroup of 165 patients who received adjuvant FOLFOX successfully (for at least 3 months), the adjusted effect of neoadjuvant chemotherapy was not significant (HR 1·19, 0·74 to 1·90; P = 0·476). No significant effect of neoadjuvant chemotherapy was observed in multivariable regression analysis. Conclusion: Compared with adjuvant chemotherapy, perioperative FOLFOX does not improve DFS in patients with resectable CLM, provided adjuvant chemotherapy is given successfully. Graphical Abstract: This study aimed to estimate the effect of neoadjuvant FOLFOX in patients undergoing upfront resectable colorectal liver metastases. After adjustment, no significant impact of FOLFOX was detected, suggesting that upfront surgery may be acceptable in patients with limited disease. No significant effect of neoadjuvant chemotherapy on disease-free survival observed